Effect of wood sawdust on pyrolytic performance of dyeing sludge: Focusing on the sulfur migration and transformation - Wang, Teng; Zhang, Qinyuan; Xiong, Qiao; Huang, Jinyu; Du, Dan; Liu, Bo; Xue, Yongjie (Separation and purification technology, 2023)
[Display omitted] •Effect of WS on pyrolysis characteristic of DS;•In-situ inhibition on gaseous sulfur under given WS dose;•Multistage model is established to evaluate the co-pyrolysis kinetic;•Migration and transformation of sulfur during co-pyrolysis of DS and WS. Dyeing sludge (DS) pyrolysis is a prospective alternative due to environment and energy considerations, however, the sulfur control remains challenge. This study selects wood sawdust (WS) as clean and carbon–neutral desulfurizer during DS pyrolysis. Co-pyrolysis characteristics and sulfurous gases emission are monitored by thermogravimetry and mass spectrometry (TG-MS), as well as the migration and transformation of sulfur is revealed by batch experiments. Results indicated that co-pyrolysis of DS and WS was mainly decomposed into devolatilization and char reaction. WS performed two-sidedness: physical scherm and catalysis. Incorporation of co-pyrolysis characteristic parameters, scherm dominated the whole pyrolysis under 30% WS condition. H2S, CH3SH and SO2 were the major contributors (>90%) for sulfurous pollutants. Output of gaseous sulfur decreased under 30% WS action, and its in-situ retention ratio could reach 23.08%. Co-pyrolysis kinetics was expressed as (1) at devolatilization stage, scherm of biochar blocked the diffusion of gases (the main sulfur control stage), (2) at char stage, formed residue was difficult to degrade into gaseous products. Co-pyrolysis biochar and tar products jointly capture gaseous sulfur. The corresponding in-situ sulfur retention mechanism were summarized as: sulfur forms were stabilized in biochar (especially via sulfation), while S-containing ester transformed into stable forms in tar.